Risk Factors of Intrauterine Growth Restriction: A Case-Control Study - Putu Jeremia Dani Bramanta; Theresia Avilla Ririel Kusumosih; Oscar Gilang Purnajati; Marie Caesarini (Indonesian Journal of Obstetrics and Gynecology, 2026)
Abstract Objectives: To explore out whether age, rate of delivery, and hypertension are risk factors for IUGR in Bethesda Hospital Yogyakarta Methods: A case control study was used by evaluating medical record of patient who diagnosed with IUGR in Bethesda Hospital Yogyakarta between January 2015 – December 2021.  Results: The sample size was 62 with a case number of 31 (IUGR) and in control patients without IUGR of 31. Based on bivariate analysis with chi square test, it was found the risk factor for IUGR was hypertension (P = 0,032; OR = 3,906). Risk factor age (P = 0,115) and rate of delivery (P = 0,446; OR = 1,681) were not found to be risk factor for IUGR. Conclusion: Hypertension is a risk factor for IUGR, whereas age and rate of delivery are not risk factors for IUGR in Bethesda Hospital Yogyakarta. Keywords: IUGR, age, rate of delivery, hypertension.